Supporting educators to implement behavior-specific praise: a research synthesis - Pérez, Paloma; Royer, David James; Buckman, Mark Matthew; Lane, Kathleen Lynne (Frontiers in Education, 2025)
We conducted a synthesis of recent systematic reviews with a specific focus on the professional learning aspects of behavior-specific praise (BSP). We examined training procedures and support types aimed at facilitating effective BSP implementation, addressing the following research questions: What procedures were used in training the intervention agent to deliver BSP? To what degree were training integrity and social validity of training procedures assessed? What feedback did intervention agents receive about their implementation of BSP (e.g., emailed graph of BSP rate; self-monitored rate of BSP)? We examined implications of these findings for informing future efforts to support educators implementing BSP, given effective implementation is a critical skill for reinforcing prosocial behaviors, fostering positive school cultures, and mitigating issues associated with exclusionary practices. Results indicated many studies included training for educators on how to implement praise and provide feedback effectively, yet few reported training integrity. We found social validity was primarily assessed in studies through surveys and interviews. Few studies included checks for understanding for educators with permanent products measuring knowledge to identify areas for support. Most studies utilized in-person and verbal BSPs, with some using notes. We discuss limitations and future directions, suggesting results from this review may be useful for informing future professional learning efforts to assist teachers in implementing BSP, a low-intensity strategy for supporting students and educators to promote a positive culture within educational settings.